Oestrus pheromones in farm mammals, with special reference to cow - VYAS, SUMANT; BRIANT, C; CHEMINEAU, P; DANVIC, C LE; MEILLOUR, P NAGNAN-LE (The Indian Journal of Animal Sciences, 2012)
Pheromones are defined as chemical signals that are released from one individual and induce specific endocrine or behavioural reactions in another individual of the same species. Odours play a significant role in signalling the stage of reproduction of the cow, and the bull can use a combination of factors displayed by the female to determine its receptivity. During oestrus, females release olfactory molecules, thus signalling the stage of their cycle and stimulating sexual behaviour and functions of males. Attempts were made to review the chemical nature of olfactory signals of oestrus in milk, urine, blood, saliva, skin gland secretion during the proestrous and oestrous cycle. Several behavioural studies indicated that bovine milk from different stages of the oestrous cycle had different odours. Bulls have also been found to detect pheromone odours and differentiate between oestrus and non-oestrus urine. Bioassay involving rats revealed the presence of maximal pheromone activity during proestrus. Vaginal fluid is also reported to act as a chemical signal. Saliva, serum, skin gland secretions and faeces have also been studied for their pheromonal properties. Systemic evaluation of either urine or vaginal secretions over the whole cycle has yet to be investigated. The use of artificial olfaction could enable more accurate detection of oestrus and potentially increase fertility in cows. The current status of chemical signals (pheromones) of oestrus and their identification in farm animals is reviewed in this article with emphasis on cows.